Carry-over body mass effect from winter to breeding in a resident seabird, the little penguin. Issue 1 (January 2015) - Salton, Marcus; Saraux, Claire; Dann, Peter; Chiaradia, André
Abstract : Using body mass and breeding data of individual penguins collected continuously over 7 years (2002–2008), we examined carry-over effects of winter body mass on timing of laying and breeding success in a resident seabird, the little penguin ( Eudyptula minor ). The austral winter month of July consistently had the lowest rate of colony attendance, which confirmed our expectation that penguins work hard to find resources at this time between breeding seasons. Contrary to our expectation, body mass in winter (July) was equal or higher than in the period before ('moult-recovery') and after ('pre-breeding') in 5 of 7 years for males and in all 7 years for females. We provided evidence of a carry-over effect of body mass from winter to breeding; females and males with higher body mass in winter were more likely to breed early and males with higher body mass in winter were likely to breed successfully. Sex differences might relate to sex-specific breeding tasks, where females may use their winter reserves to invest in egg-laying, whereas males use their winter reserves to sustain the longer fasts ashore during courtship. Our findings suggest that resident seabirds like little penguins can also benefit from a carry-over effect of winter body mass on subsequent breeding.